Comparative mechanical, thermal properties and morphological study of untreated and NaOH-treated coconut shell-reinforced cardanol environmental friendly green composites. Issue 16 (17th August 2020) - Udhayasankar, R.; Karthikeyan, B.; Balaji, A.
Abstract: High-performance materials from natural resources have gained momentum worldwide. Present study concentrated and carried out to prepare six sets of cardanol-based biocomposites in combination with coconut shell particles (CSP) with an average size of 25, 50 and 75 μm which have been treated and untreated chemically with biopolymer. The particles have been blended in various wt% (viz., 0, 10, 20, 30 and 40 wt%) with cardanol. For the development of the composites, the tensile strength, flexural strength and impact test have been carried out to study the mechanical properties. By using the scanning electron microscopy (SEM) the morphological study (in flexural fractured specimens) has also been conducted. The chemical formation of the new biocomposites was also examined by the FT-IR spectroscopy technique. In addition to this, differential scanning calorimeter (DSC) tests were also conducted. And the final results proved that the morphologies of the composites seemed to have an improved bonding between the filler and the resin, which led to enhanced mechanical properties. Among the six sets, 30 wt% of 25 µm NaOH-treated CSP composite was a chosen one, which has better mechanical properties with higher tensile strength; flexural strength, impact strength and thermal stability than the other sets. After having scanned the microscopy examination, it has been revealed that there was a mechanism of the strength gain with regard to the morphological point of view. Mechanical and thermal stability of the composite enhanced suitable response due to a decrease in particle size with alkaline treatment.